Challenges and solutions in meeting up the urgent requirement of ventilators for COVID-19 patients (2020)
Background Severely affected patients in the COVID-19 pandemic need Ventilators, we chart the challenges faced by the health care systems in procuring these machines and the role of 3-D printing technology in building ventilators. Aims We tried to find the current role, availability and need of ventilators in the COVID-19 pandemic and the role of applied innovative technologies is assessed. Methods We have done a comprehensive review of the literature using suitable keywords on the search engines of PubMed, SCOPUS, Google Scholar and Research Gate in the second week of April 2020. Results We found in our review that there is an acute shortage of the ventilators and the manpower to operate these sophisticated machines. There is significant deficiency in the production and supply chain of the ventilators. Many of the seriously ill patients who require hospitalization may need ventilator support. Non-invasive ventilation is not recommended in these patients. Conclusion As the respiratory illness due to COVID-19 pandemic spreads worldwide, health care systems are facing the tough challenges of acquiring ventilators to support patients. All steps involved in the supply chain management of ventilators are being escalated to produce more ventilators for the coronavirus frontline. Innovative applications of Additive medicine like 3-D printer technology may play key role in delivering sufficient ventilators.